A Convergence of Minds: Teilhard de Chardin and Conway Morris - Hart, Seth P. (Theology and science, 2021)
While the work of Simon Conway Morris has garnered significant attention, very little has been paid to the overlap between his thought and the work of Pierre Teilhard de Chardin. Thus, I first detail the development of Conway Morris’s thought and note his “theological turn.” I then compare this with Teilhard’s evolutionary theology, establishing a broad conceptual overlap. Lastly, I demonstrate Conway Morris’s written engagement with and admiration for Teilhard’s work during his theological turn and conclude that Conway Morris’s later works have been impacted by Teilhardian thought. Consequently, this merits Teilhard’s inclusion in contemporary discussions of convergence and teleology.